Natural occurrence of subjective aging experiences in community-dwelling older adults - Gabrian, Martina; Wahl, Hans-Werner; Diehl, Manfred; Oswald, Frank; Kaspar, Roman; Kolb, Maren (The journals of gerontology. Series B, Psychological sciences, social sciences, 2014)
The subjective experience of aging is a relevant correlate of developmental outcomes. However, traditional approaches fall short of capturing the inherent multidimensionality of subjective aging experiences (SAEs). Based on the concept of Awareness of Age-Related Change (AARC; Diehl, M. K., & Wahl, H.-W. (2010). Awareness of age-related change: Examination of a (mostly) unexplored concept. Journals of Gerontology: Series B: Psychological Sciences and Social Sciences, 65, 340-350. doi:10.1093/geronb/gbp110), this study provides a description of SAEs that is facet rich, and based on their natural occurrence, analyzes interindividual differences and associations with well-being.Data came from 225 participants (70-88 years) of the ongoing BEWOHNT study. Open-ended diary entries about age-related experiences were collected for more than 14 days and coded according to AARC domains and subdomains.Seventy percent of all participants had SAEs about physical functioning. About half of the sample reported experiences in the domains interpersonal relations, social-emotional and social-cognitive functioning (COGN-EMOT), and lifestyle. Thirty percent experienced aging in terms of changes in cognitive functioning. Contents of SAEs varied by gender, age group, and functional status. SAEs about COGN-EMOT were most consistently related to affective components of subjective well-being.Our results demonstrate the benefits of an open-ended approach to a multidimensional understanding of SAEs. Content-related, social-cognitive and social-emotional changes more than functional age-related changes were most important for well-being.
Published: 16 January 2013
Gesehen am 30.06.2016